1992
DOI: 10.1038/sc.1992.160
|View full text |Cite
|
Sign up to set email alerts
|

New estimates of the direct costs of traumatic spinal cord injuries: results of a nationwide survey

Abstract: New estimates of the direct costs of traumatic spinal cord injuries (SCI) are obtained from a comprehensive survey of the US SCI population. These direct costs, defined as the value (in 1988 dollars) of resources used specifically to treat or to adapt to the SCI condition, represent the average experience of the US SCI population. Responses to a detailed questionnaire administered to a sample of traumatic SCI persons in the United States provide the primary source of data for this study. Analysis of this surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 3 publications
2
48
0
6
Order By: Relevance
“…Prior studies have included those with paraplegia, and people with these lower-level injuries have been found to experience fewer rehospitalizations. 10 One survey-based study that included predominately tetraplegia cases (93%) produced results similar to those of the current study, reporting that 57% had at least one rehospitalization in the year prior to the survey. 2 Another survey-based study that reported on those with tetraplegia, found that 41.5% of those with complete lesions and 35% with incomplete lesions were rehospitalized the year prior to the survey.…”
Section: -220 921supporting
confidence: 73%
“…Prior studies have included those with paraplegia, and people with these lower-level injuries have been found to experience fewer rehospitalizations. 10 One survey-based study that included predominately tetraplegia cases (93%) produced results similar to those of the current study, reporting that 57% had at least one rehospitalization in the year prior to the survey. 2 Another survey-based study that reported on those with tetraplegia, found that 41.5% of those with complete lesions and 35% with incomplete lesions were rehospitalized the year prior to the survey.…”
Section: -220 921supporting
confidence: 73%
“…This claim has been challenged by other studies. In terms of neurologic outcome, the field of SCI research is torn between substantive evidence from preclinical animal models favoring early surgery [29,31,48] and mixed evidence from human clinical trials. Recent preliminary results from the Surgical Treatment for Acute Spinal Cord Injury Study (STASCIS) suggest decompression of the spinal cord within 24 hours of injury is associated with improved neurologic recovery in persons with cervical injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…This number must be interpreted with reference to a complete picture of this devastating condition: a substantial number of individuals who sustain a SCI die before reaching the hospital; patients who do reach the hospital have complications related to their injury and are at high risk of morbidity and mortality; the economic costs of this injury are estimated in the billions of dollars in developed countries (United States); and the personal and family suffering is incalculable [2,29,54]. Those sustaining SCI tend to be either young individuals sustaining traumatic injury at the prime of their personal lives and economic earning potential or older individuals who sustain falls.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since then, the only information captured by the NSCID relevant to services provided following SCI is: acute hospital care and rehabilitation length of stay and associated charges while in the Model SCI care system, length of readmission, time spent in nursing homes, and sponsors of care. 1 While researchers in the 1990s conducted studies investigating the economic cost of SCI and published several papers on this topic, [1][2][3][4] there have been no recent updates.…”
Section: Introductionmentioning
confidence: 99%